Comparative analysis of metagenomic and targeted next-generation sequencing for pathogens diagnosis in bronchoalveolar lavage fluid specimens - Sun, Weijie; Zheng, Lin; Kang, Le; Chen, Chen; Wang, Likai (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundAlthough the emerging NGS-based assays, metagenomic next-generation sequencing (mNGS) and targeted next-generation sequencing (tNGS), have been extensively utilized for the identification of pathogens in pulmonary infections, there have been limited studies systematically evaluating differences in the efficacy of mNGS and multiplex PCR-based tNGS in bronchoalveolar lavage fluid (BALF) specimens.MethodsIn this study, 85 suspected infectious BALF specimens were collected. Parallel mNGS and tNGS workflows to each sample were performed; then, we comparatively compared their consistency in detecting pathogens. The differential results for clinically key pathogens were confirmed using PCR.ResultsThe microbial detection rates of BALF specimens by the mNGS and tNGS workflows were 95.18% (79/83) and 92.77% (77/83), respectively, with no significant difference. mNGS identified 55 different microorganisms, whereas tNGS detected 49 pathogens. The comparative analysis of mNGS and tNGS revealed that 86.75% (72/83) of the specimens were complete or partial concordance. Particularly, mNGS and tNGS differed significantly in detection rates for some of the human herpesviruses only, including Human gammaherpesvirus 4 (P<0.001), Human betaherpesvirus 7 (P<0.001), Human betaherpesvirus 5 (P<0.05) and Human betaherpesvirus 6 (P<0.01), in which tNGS always had higher detection rates. Orthogonal testing of clinically critical pathogens showed a total coincidence rate of 50% for mNGS and PCR, as well as for tNGS and PCR.ConclusionsOverall, the performance of mNGS and multiplex PCR-based tNGS assays was similar for bacteria and fungi, and tNGS may be superior to mNGS for the detection of DNA viruses. No significant differences were seen between the two NGS assays compared to PCR.